Zadania podmiotów cywilnych w zakresie dyplomacji obronnej. Przykład polskich think tanków .......... 187 - Olszyk, Sabina (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The change in character and ways of using military force in international politics at the end of the 20th century has produced new methods of cooperation leading to the formation of defense diplomacy. In the new reality, the group of entities conducting diplomatic activities has expanded and has become increasingly diverse. In addition to political and military actors, also non-governmental entities, i.e. NGOs, business institutions and expert centers, began to undertake diplomatic activities. This raised questions, among others, about the scale of the impact of these entities on the creation of the international situation and the shaping of defense policy of countries? What tasks in the field of defense diplomacy are carried out to the highest / lowest degree? Which of the expert centers carry out particular tasks to the highest degree? This study in an attempt to answer the above questions. The analysis was based on data obtained as a result of surveys and the analysis of websites of fifteen Polish expert centers (think tanks) operating in the field of international relations, political sciences as well as security and defense.